Incidence and prevalence of autoimmune hepatitis in the Ueda area, Japan. Issue 9 (11th January 2016) - Yoshizawa, Kaname; Joshita, Satoru; Matsumoto, Akihiro; Umemura, Takeji; Tanaka, Eiji; Morita, Susumu; Maejima, Toshitaka; Ota, Masao
Abstract : Aim: Although autoimmune hepatitis (AIH) is considered to be rare in Japan, precise data on the incidence and prevalence of this disease are scarce due to the lack of a nationwide registry. We therefore conducted a study of these factors over a secondary medical care area. Methods: We retrospectively investigated the medical records of AIH patients seen during 2004–2009 and prospectively recruited subjects from 2010 to 2014 at our hospital. We surveyed via written questionnaires to all family doctors and hospitals in our secondary medical care area of Ueda, with a population 187 205 individuals over 14 years of age. We also surveyed several core liver disease hospitals in the areas neighboring Ueda. Results: Forty‐eight patients with AIH were diagnosed between 2004 and 2014. AIH with histological features of acute hepatitis was increased. The average annual incidence of AIH in the area was 2.23 (age‐standardized to the Japanese population). Forty‐eight patients (37 patients diagnosed between 2004 and 2014, and 11 patients before 2003) were followed to the study end‐point. The prevalence was 23.4 (age‐standardized to the Japanese population) on 31 December 2014. After age‐standardization to the World Health Organization world standard population, the incidence and prevalence of AIH decreased to 1.52 and 15.0, respectively, likely due to the high proportion of elderly patients in Japan. Conclusion: The incidence and prevalence of AIH in Japan may be higher than previously believed due to increased awareness among family doctors, and a rise in the diagnosis of mild or atypical AIH.